Effectiveness of multimodal dental health education with animated cartoons for improving knowledge, attitudes, oral hygiene practices and reducing dental plaque in 7-9 year-old children in Khon Kaen Province - Nguanjairak, Rachanon; Duangsong, Rujira; Patcharanuchat, Piyachat; Muangsom, Niramon; Bradshaw, Peter (Journal of Public Health and Development, 2017)
Good oral care in children, especially in those aged 7 to 9 years, is important if the risks of later serious dental carries and periodontal health problems are to be minimised. The purpose of this study was to evaluate the effectiveness of an innovative multimodal education programme, which included the use of animated cartoons, to improve knowledge, attitudes and oral hygiene practices of children among this critical age group. The present study was a cluster randomised controlled trial involving a total of 244 children selected from elementary classes in two districts in Khon Kaen Province, Thailand. The children in one district received the multimodal education programme, while the other district provided the no-treatment controls. The outcome variables comprised measures of dental health knowledge, attitudes to oral care, reported oral hygiene practices, and an objective assessment of plaque formation. Data were analysed using multiple logistic regression with a generalised estimating equation to estimate effect sizes in the intervention and control groups. When compared with the controls, the new education programme resulted in statistically significant improvements in all the outcome variables including plaque formation which was the most objective measure of dental care. Recommendations were made for future research. Two important limitations of the study are noted: the exact contribution of each of the multimodal programme components remains unknown, in particular the use of animated cartoons, and the lack of a long-term follow-up.